Physical Principles of Biomembranes and Cells - Ohki, Kazuo (Biological and Medical Physics, Biomedical Engineering,, 2018)
This book describes how biologically available free energy sources (ATP, chemical potential, and membrane potentials, among others) can be used to drive synthetic reactions, signaling in cells, and various types of motion such as membrane traffic, active transport, and cell locomotion. As such, it approaches the concept of the energy cycle of life on Earth from a physical point of view, covering topics ranging from an introduction to chemical evolution, to an examination of the catalytic activity of enzymes associated with the genome in Darwinian evolution. The author introduces the relationship between functions and physical properties in biomembranes, explaining the methods and equipment used in biophysics research to help researchers unravel the still-unsolved mysteries of life. The physical principles needed to understand the cellular functions are provided; these functions are associated with biomembranes and regulated by physical properties of the lipid bilayer such as membrane fluidity, phase transition, and phase separation, as shown in lipid rafts. Other key dynamic aspects of life (cell locomotion, cytoskeletal dynamics, and sensitivities of the cell to physical stimuli such as external forces and temperature) are also discussed. Lastly, readers will learn how life on Earth and its ecological system are maintained by solar energy, and be provided further information on the problems accompanying global warming.